Studi Regangan Axial dan Lateral pada Tanah Ekspansif - Fitriyana, Lisa; Rochim, Abdul (Semarang State University, 2017)
Swelling and shrinkage abilities of soils are dangerous for buildings. According to Hardiyatmo (2014) There are two types of swelling in expansive soils that are the movement of lateral (horizontal) and axial (vertical). Oftentimes the deformation of soils cannot be supported by building stiffness. This damage can be seen in retaining walls, tunnel walls, and etc. With the aims to identify an expansive soil and to know its lateral and axial strains, an experimental study was performed. Swelling tests were conducted in a specimen having diameter (d) of 4,5 cm and height Â (h0) ofÂ 2 cm with the variations in : 1) water content wopt = 31% and 18%; 2) vertical pressure (pv) 1 kPa, 3.5 kPa and 6.9 kPa; and 3) membrane thickness (t) 0.7 mm and 0.5 mm. The strain in the axial direction was measured with a dial gauge that was set vertically parallel whereas the lateral strain is by measuring changes in diameter of the specimen with a digital caliper measurement tools. Based on the analysis on the identification results, the observed soil is classified as expansive soil with the expansion potential is high average. The test results show the same potential for the occurrence of lateral and lateral strain if the lateral retention (e.g. retaining wall) is weak. The largest lateral and axial soil development occurred at water content w0 = 18% are 15.7% and 15.8% respectively.Â